2014
DOI: 10.1093/aje/kwu036
|View full text |Cite
|
Sign up to set email alerts
|

Daytime Napping and the Risk of All-Cause and Cause-Specific Mortality: A 13-Year Follow-up of a British Population

Abstract: Epidemiologic studies have reported conflicting results on the relationship between daytime napping and mortality risk, and there are few data on the potential association in the British population. We investigated the associations between daytime napping and all-cause or cause-specific mortality in the European Prospective Investigation Into Cancer-Norfolk study, a British population-based cohort study. Among the 16,374 men and women who answered questions on napping habits between 1998 and 2000, a total of 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
115
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 113 publications
(129 citation statements)
references
References 39 publications
9
115
0
Order By: Relevance
“…Some studies have reported that napping is associated with a higher risk for diabetes and all-causes mortality among older adults. 27,28 In line with previous cross-sectional studies showing a positive relationship of longer napping with a higher risk for MetS, 10,29 we found that excessive napping ( ≥ 90 min) was also an independent predictor of incident MetS and might exert an adverse effect on the MetS reversion. Nonetheless, the findings should be interpreted cautiously because we did not see any significant difference between napping categories and incidence or reversion of MetS components.…”
Section: Discussionsupporting
confidence: 90%
“…Some studies have reported that napping is associated with a higher risk for diabetes and all-causes mortality among older adults. 27,28 In line with previous cross-sectional studies showing a positive relationship of longer napping with a higher risk for MetS, 10,29 we found that excessive napping ( ≥ 90 min) was also an independent predictor of incident MetS and might exert an adverse effect on the MetS reversion. Nonetheless, the findings should be interpreted cautiously because we did not see any significant difference between napping categories and incidence or reversion of MetS components.…”
Section: Discussionsupporting
confidence: 90%
“…We did not perform sensitivity and subgroup analyses for the association between daytime napping and cancer mortality because of few included studies. For studies that reported HRs separately for men and women [8,16,[23][24][25], or for different napping duration ranges [9,16,19], we employed a randomeffects model to yield overall estimates for our meta-analysis.…”
Section: Discussionmentioning
confidence: 99%
“…The frequency of napping usually increases with age [3][4][5][6], and it is higher in men than that in women [6,7]. Traditionally, daytime napping is usually considered a healthy habit, and it is often linked with the low incidence of coronary heart disease and high tendency of longevity [8] through a hypothetical "stress relief" mechanism [9] in Latin American and Mediterranean countries. The Chinese believe that daytime napping is complementary to nighttime sleep, and hence a beneficial behavior.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations